Comparison of levels of serum copper, zinc, albumin, globulin and alkaline phosphatase in psoriatic patients and controls: A hospital based casecontrol study - Gousia Sheikh; Qazi Masood; Sabiya Majeed; Iffat Hassan (Wolters Kluwer Medknow Publications, 2015)
Background: Psoriasis is a chronic, immune-mediated skin disease with unknown etiology, with an epidermal turnover time of <10 days compared to a normal turnover time of 4-8 weeks. This epidermal hyperproliferation accounts for many of the metabolic abnormalities including alteration in the serum levels of proteins and some trace elements. Aim: The aim was to detect any statistically significant difference in the serum levels of zinc, copper, albumin, globulin and alkaline phosphatase between psoriasis patients and healthy controls. Materials and Methods: Hundred cases of psoriasis and 100 age and sex matched controls were enrolled in a hospital based case-control study. The serum levels of zinc, copper, albumin, globulin and alkaline phosphatase were calculated and compared among the cases and controls and evaluated statistically. Results: Serum zinc levels were significantly low in the psoriasis group as compared with controls (mean 80.028 μg/dl vs. 109.179 μg/dl, P < 0.0001). Serum copper levels were significantly raised among cases as compared with controls (mean 167.317 μg/dl vs. 133.884 μg/dl P < 0.0001). Serum albumin levels were significantly decreased (3.762 g/dl vs. 4.103 g/dl, P < 0.001), whereas serum globulin levels were raised (3.296 g/dl vs. 2.596 g/dl, P = 0.0014) among cases as compared with controls, respectively. Serum alkaline phosphatase levels were comparable between the two groups. Conclusion: The results of this study show significant alterations in the serum levels of copper, zinc, albumin, and globulin in psoriatic patients. This paper aims at highlighting the possible role of trace metals copper and zinc in the aetiopathogenesis of psoriasis and also provides a proposed interplay of factors involved in the pathogenesis of psoriasis.